2015
DOI: 10.1108/s2055-364120150000003027
|View full text |Cite
|
Sign up to set email alerts
|

Problem Finding through Design Thinking in Education

Abstract: Design thinking has become something of a buzz word in innovation discussions and has recently also invested occupied education spaces. In this chapter we briefly compare design thinking to problem-based learning (PBL) and enquiry-based learning (EBL) approaches to problem solving in education before focusing on the approach itself and current debates about its meaning and significance. This chapter focuses particular attention on the problem finding aspect of design thinking and its integration of creative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…The principles of user focus, problem framing, visualization, experimentation, and diversity constitute what research has identified as key practices for tackling management challenges in turbulent times (Bicen & Johnson, 2015; Melles et al, 2015). Teaching management students this essence of design thinking is thus one way of preparing them to deal with real-world turbulence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The principles of user focus, problem framing, visualization, experimentation, and diversity constitute what research has identified as key practices for tackling management challenges in turbulent times (Bicen & Johnson, 2015; Melles et al, 2015). Teaching management students this essence of design thinking is thus one way of preparing them to deal with real-world turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…Melles, Anderson, Barrett, and Thompson-Whiteside’s (2015) case study analysis shows the generative potential of design thinking, particularly for students from nondesign disciplines. They find this potential a particular strength of the design-thinking approach, complementing existing pedagogies and inspiring change and innovation.…”
Section: Managing Turbulent Contexts and Design Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…'The Design thinking process begins with a problem finding process that engages with the world around to discover needs and insights that might drive the innovation of products, services or systems of various scales and complexities' (Melles et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Design is considered as an accessible structure to think creatively about educational problems (Henriksen et al, 2017) and curriculum renewal (Melles et al, 2012). Studies have outlined the potential of design for all students, from primary to university level (Grammenos and Antona, 2018;Melles et al, 2015). In design-based curricula, students are expected to gain skills such as collaboration, problem solving and empathy.…”
Section: Introductionmentioning
confidence: 99%